Pengaruh IPM Dan Upah Minimum Terhadap Kemiskinan Dengan ZIS Sebagai Variabel Moderating Di Provinsi Jawa Tengah - Tarida, Ade Kamilatu; Nurhadi, Bayu (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
This research aims to find out how the Human Development Index (HDI) and minimum wage relate to poverty with ZIS as a moderate variable in Central Java Province in 2018-2023. This research uses quantitative methods with secondary data taken from the BPS and BAZNAS website. The data used is combined panel data from time series data from 2018-2023 and cross section data from 35 districts/cities in Central Java Province with sampling using a saturated sampling tachnique. The data analisys tool used is Eviews 10. The research results show that HDI has a negative and significant influence on poverty, while the minimum wage has a positive and significant influence on poverty. Meanwhile, the ZIS variable is unable to moderate the relationship between HDI and munimum wages on poverty in Central Java Province in 2018-2023.